1973
DOI: 10.1002/j.1551-8833.1973.tb01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Alum Sludge Thickening and Disposal

Abstract: It has been customary for water‐treatment plants using chemicals in the water‐treatment process to discharge waste sludge into a nearby natural water course. This practice is coming under increasing criticism from both the public and water‐quality agencies and is now becoming subject to regulation. This article describes pilot work subsequent to the receipt of specific discharge requirements set by the Regional Water Quality Control Bd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…4 Nielsen et al (1973) found that after drying alum sludge at 103°C, 1.25H 2 O molecules per molecule of Al(OH) 3 remained. 5 This means that under steady state operation, the alum dosing location within the bioreactor is not critical; no saving of alum accrues from dosing in the anaerobic reactor where PO 4 is higher as the P is released again downstream where PO 4 concentrations are lower.…”
Section: Phosphorus Removalmentioning
confidence: 96%
“…4 Nielsen et al (1973) found that after drying alum sludge at 103°C, 1.25H 2 O molecules per molecule of Al(OH) 3 remained. 5 This means that under steady state operation, the alum dosing location within the bioreactor is not critical; no saving of alum accrues from dosing in the anaerobic reactor where PO 4 is higher as the P is released again downstream where PO 4 concentrations are lower.…”
Section: Phosphorus Removalmentioning
confidence: 96%